Long‐term observation on hepatitis B surface antigen seroclearance in therapy experienced HIV/HBV co‐infected Chinese. Issue 2 (28th October 2019) - Yang, Rongrong; Gui, Xien; Ke, Hengning; Xiong, Yong; Gao, Shicheng
Abstract: The aim of this retrospective study was to observe hepatitis B surface antigen (HBsAg) seroclearance and explore predictors of HBsAg loss in HIV/HBV‐co‐infected patients receiving long‐term lamivudine or both tenofovir and lamivudine containing therapies. Quantification of HBsAg, hepatitis B e antigen and HBV DNA before and after initiation of HBV‐active antiretroviral therapy in a total of 268 HIV/HBV‐co‐infected patients started treatment between 2005 and 2017 were performed. Over a median of 65.63 months of follow‐up, 10 (3.7%) were observed HBsAg loss and the quantification of HBsAg in 7 (2.6%) patients were less than 50 IU/mL. With the prolongation of antiretroviral therapy duration time, the rates of HBsAg seroclearance tended to increase gradually, rising from 1.8% (3/163) during 2‐4 years treatment to 29.4% (10/34) after antiretroviral therapy for up to 10 years. Lower baseline qHBsAg and HBV DNA levels and strong 12‐month declines in qHBsAg were significantly associated with HBsAg seroclearance. The event of HBsAg seroclearance is uncommon among Chinese individuals with HIV/HBV co‐infection who have been treated with anti‐HBV containing antiretroviral therapy, and lifelong therapy for HBV is needed for HIV/HBV co‐infected patients. Baseline qHBsAg and HBV DNA levels and qHBsAg decline rate were predictors for HBsAg seroclearance.